2014
DOI: 10.1371/journal.pone.0097521
|View full text |Cite
|
Sign up to set email alerts
|

Health-Care-Seeking Patterns in the Emerging Private Sector in Burkina Faso: A Population-Based Study of Urban Adult Residents in Ouagadougou

Abstract: BackgroundThe private medical care sector is expanding in urban cities in Sub-Saharan Africa (SSA). However, people’s health-care-seeking behaviors in this new landscape remain poorly understood; furthermore, distinguishing between public and private providers and among various types of private providers is critical in this investigation. This study assessed, by type, the healthcare providers urban residents in Burkina Faso visit, and their choice determinants.MethodWe conducted a population-based survey of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 63 publications
5
23
0
Order By: Relevance
“…Finally the utilization of private for pro t health facilities has been shown in previous research to be dependent on factors such as insurance coverage, high education level, and being a formal job holder (20). These ndings are consistent with our results which similarly indicate that education, health-insurance, monthly income and socio-economic status are strong predictors of where care is usually accessed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally the utilization of private for pro t health facilities has been shown in previous research to be dependent on factors such as insurance coverage, high education level, and being a formal job holder (20). These ndings are consistent with our results which similarly indicate that education, health-insurance, monthly income and socio-economic status are strong predictors of where care is usually accessed.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, better educated and wealthier participants in a Ghanaian based study were signi cantly more likely to visit private health facilities compared to public health facilities (22). Importantly, given the context of this current study, controlling for health-insurance was previously found to lessen the in uence of factors such as education and occupation (20). Our study reveals that potential impact on volumes could mean that while most high visit frequency patients currently access care in the public sector, a portion of these visits may be distributed to the private sector under NHI which might result in more than the estimated three annual visits per person per year (23) (24).…”
Section: Discussionmentioning
confidence: 65%
“…They consist of for-profit (FP) and non-for-profit providers (NFP); the former are defined as benefit-focused and the latter include philanthropic medical institutions. Institutional stewardship is further considered to complete the definition of the private healthcare sector, because in LMICs, services delivered in the private sector may be publicly financed—commonly in NFP [42]. …”
Section: Methodsmentioning
confidence: 99%
“…The foundations of Universal Health Coverage are grounded in public healthcare systems, yet private healthcare services play a crucial role in contributing to healthcare delivery in many lower-income countries [17], and are expanding in sub-Saharan Africa [18]. Examining factors associated with the type of outpatient healthcare provider among older adults may help to improve health service delivery and health system governance.…”
Section: Introductionmentioning
confidence: 99%